Report on the 2nd Ibero-American Conference on Electronic Publishing in the Context of Scholarly Communication (CIPECC 2008) - Baptista, Ana Alice (2009)
[Extract] IBICT (the Brazilian Institute for Information in Science and Technology) hosted the second edition of CIPECC, from 17-21 November 2008 in Rio de Janeiro, Brazil. This biennial conference series accepts works and communications both in Portuguese and Spanish. A full day of pre-conference workshops was held on 17 November. The themes were vast and interesting for almost anyone working in information science, with topics ranging from Digital Preservation (by Miguel Ángel Arellano - Brazil) to the Social Web (by Ewout ter Haar and Everton Alvarenga - Brazil). The SciELO team, represented by Rogério Mugnaini (Brazil), held a workshop in bibliometrics,1 and Robson Almeida (Brazil) held a workshop on RSS feeds and their usage within the context of Scholarly communication...